1375. In vitro Activity of Cefiderocol and Comparator Agents against Gram-Negative Isolates from Cancer Patients. (26th November 2018) - Rolston, Kenneth V I; Gerges, Bahgat; Raad, Issam; Aitken, Samuel L; Reitzel, Ruth; Prince, Randall
Abstract: Background: Gram-negative bacilli (GNB) are now the predominant cause of bacterial infection in cancer patients (CP). Many GNB are problematic because they have become resistant to commonly used antibiotics. Cefiderocol (CFDC), a novel siderophore cephalosporin, is active against a wide spectrum of GNB. We evaluated its in vitro activity and that of eleven comparator agents against GNB isolated from CP. Methods: A total of 341 recent GNB blood isolates from CP were tested using CLSI approved methods for MIC determination by broth microdilution. Comparator agents were amikacin (A), aztreonam (AZ), ceftazidime (CZ), ceftazidime/avibactam (CAV), cefepime (CEF), ciprofloxacin (CIP), colistin (CL), meropenem (MR), ceftolozane/tazobactam (C/T), tigecycline (TG), and trimethoprim/sulfamethoxazole (T/S). Results: CFDC MIC90 s as mg/L were: S. maltophilia [50 isolates] 0.25, E. coli (ESBL−) [50 isolates] 0.5, E. coli (ESBL+) [51 isolates] 2.0, K. pneumoniae (ESBL− and +) [60 isolates] 0.5; K. pneumoniae (CRE) [22 isolates] 2.0 ; P. aeruginosa (MDR) [32 isolates] 1.0; E. cloacae [27 isolates] 4.0; Achromobacter spp. [15 isolates] 0.12. CFDC inhibited P. agglomerans, Burkholderia spp., Sphingomonas spp., Ochrobactrum spp. at ≤1 mg/L [23 total isolates] and Elizabethkingia spp. and R. radiobacter at ≤8 mg/L [11 total isolates]. Among comparator agents, only T/S had consistent activity against S. maltophilia . For E. coli (ESBL− and +) MR, TG, CAV, CL were most active. For K. pneumoniae (ESBL–and +) MR, CAV were most active. For K. pneumoniae (CRE) and P. aeruginosa (MDR), none of the comparators had significant activity. For E. cloacae, MR, A, CAV, TG were most active. Among the uncommon organisms, MR and TG had the greatest activity. Conclusion: Although susceptibility breakpoints have yet to be determined, CFDC has significant activity (≤4 mg/L) against most problematic Gram-negative organisms causing infections in CP based on available pharmacokinetic/pharmacodynamic data. In particular, its activity against S. maltophilia was superior to the comparators. Also, it was the most active agent against P. aeruginosa (MDR) and K. pneumoniae (CRE). Based on our results, CFDC warrants clinical evaluation for the treatment of blood stream infections caused by GNB in CP. Disclosures: K. V. I. Rolston, Merck: Investigator, Research grant; JMI Laboratories: Investigator, Research grant; Shionogi (Japan): Investigator, Research grant. B. Gerges, Shionogi: Collaborator, Research support. S. L. Aitken, Shionogi: Scientific Advisor, Consulting fee; Merck: Scientific Advisor, Consulting fee; Medicines Co: Scientific Advisor, Consulting fee; Achaogen: Scientific Advisor, Consulting fee; Zavante: Scientific Advisor, Consulting fee; R. Prince, Shionogi: Investigator, Research support. Merck: Investigator, Research support.